User Interface Stereotypes: A Model-Based Approach for Information Systems User Interfaces - da Costa, Sofia Larissa; Graciano Neto, Valdemar Vicente; de Oliveira, Juliano Lopes; Calçado, Bruno dos Reis (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2014: Anais do X Simpósio Brasileiro de Sistemas de Informação, 2014)
This paper presents a model-based approach to build Information Systems User Interfaces (ISUI). In this approach, UI presentation and behavioral aspects are modeled as UI Stereotypes, which are high level abstractions of UI appearance and interaction features. A taxonomy of ISUI elements is proposed as the basis for definition of UI stereotypes. These elements are orchestrated on a software architecture which manages model-based UI building and integration with the IS applications. The proposed approach reduces software development efforts and costs, facilitating maintenance and evolution of ISUI. Moreover, UI stereotypes improve usability, consistency, reuse and standardization of both presentation and behavior of ISUI.